Experimental and Numerical Determination of Limit Velocity for Plasma Thruster (Global Journal of Science Frontier Research, 2023)
The measurement of a mechanical impulse of the plasma thruster has been performed using by the well-known magneto plasma compressor assembly MPC and features of the convergence nozzle Based on previous research 6 hydrogen had selected as a working gas from the reason that it can produce the highest velocity of plasma Because of the magneto hydrodynamics model MHD it is entirely possible to perform rules for fluid dynamics to electromagnetism with appropriate analog Using all the mentioned tools it can be determined limit value for plasma speed like analogue to sound speed and according to define the value of the analog Mach number for plasma Such that would have far-reaching consequences because it would greatly facilitate feature research and the construction of plasma thrusters Occurrence of velocity saturation indicates congestion of the nozzle which arises as a consequence of the convergence of the nozzle and this saturation is the velocity value corresponding to the limiting speed of plasma at a current circumstance As the result is in agreement with the initial hypothesis and the dependence is also confirmed with the derived formula we can conclude that exists uniform relation between occurrences also this occurrence are universal law of nature Also it is necessary to emphasize the importance of finding formula for the velocity field which have been proved by numerical methods